The Breakthroughs in Cancer Immune Checkpoint Based Therapy: A Review of Development in Immune Checkpoint Study and its Application - Huang, Yao; Liang, Dong; Liu, Jingfeng; Zeng, Jinhua; Zeng, Yongyi (Combinatorial Chemistry & High Throughput Screening, 2017)
Recently, immunotherapy has attracted more attentions to fight cancer due to its selectivity, long lasting effects, and demonstrated better overall survival and tolerance, when compared to patients treated with conventional chemotherapy or radiotherapy alone. The anti-tumor response of patient with cancer is improved either by increasing the effector cell number, the production of soluble mediators, or by modulating the host's immune checkpoint. Over the last decades, many new approaches in immunotherapy have been developed, such as immune checkpoint inhibitors, chimeric antigen receptor T cells (CART), specific T-cell -receptor T cells (TCRT) and cancer vaccine, some of which has been approved by FDA to treat several cancer types. Among them, immune checkpoint based therapy has shown tremendous promise in both solid and hematological malignancies, and has significantly improved overall survival in patients with advance cancer. Many immuno checkpoints has been discovered and demonstrated. However, there is still lack of a complete summary for them. Thus, the present review focuses on immune checkpoint study and their latest application.
Keywords: Immunotherapy